Statistical experiment analysis of wear and mechanical behaviour of abaca/sisal fiber-based hybrid composites under liquid nitrogen environment - L, Natrayan; Surakasi, Raviteja; Paramasivam, Prabhu; Dhanasekaran, Seshathiri; S., Kaliappan; Patil, Pravin P. (Frontiers in Materials, 2023)
Composite materials are increasingly replacing synthetic fiber combinations in various applications. However, certain extreme environments on Earth and in space require structures to operate under low temperatures, specifically cryogenic conditions, which can significantly affect material reactions. Therefore, the main focus of this study is to develop and evaluate hybridized biocomposites, specifically assessing their tensile, bending, and impact strengths in a controlled liquid nitrogen environment (77 K). Utilizing the Taguchi optimization method, the statistical analysis of wearing characteristics was carried out utilizing cryogenic treatment hours, load, sliding distance, and weight percentage of abaca and sisal fibers. When 20 percent abaca and sisal were mixed, tensile performance increased from 28.96 MPa to 36.58 MPa. Likewise, the same mixture increased bending strength from 59.63 MPa to 75.68 MPa, and impact strength improved from 59.36 J/m to 71.25 J/m. The cryogenic treatment of composite materials for 15 to 30 minutes improved the mechanical characteristics of the materials by enhancing the binding between reinforcements and substrate. The Taguchi 27 test outcomes showed a decreased friction coefficient of 7.79 ×105 mm3/Nm in the tenth trial with 30 minutes of cold working, 10% hybrid fibers, 600 m slide distance, and a 4 N load combination. Frictional coefficient data indicated the lowest rate during the third experiment with 15 minutes of cryogenic treatment, 10% hybrid fibers, 1500 m slide length, and a 12 N load combination. The microstructural analysis of the fractured specimen was evaluated by scanning electron microscopy. Finally, such composite materials are employed in liquid propellant tanks, satellites, spaceships, rocket constructions, aeroplane components at cruising altitudes, and other applications.